2008
DOI: 10.1002/jcla.20254
|View full text |Cite
|
Sign up to set email alerts
|

Nontreponemal tests in the diagnosis of neurosyphilis: an evaluation of the Venereal Disease Research Laboratory (VDRL) and the Rapid Plasma Reagin (RPR) tests

Abstract: The Venereal Disease Research Laboratory (VDRL) test has long been considered the best serological test for the diagnosis of neurosyphilis. The goal of this study was to find out if the Rapid Plasma Reagin (RPR) could be an alternative to the VDRL. Cerebrospinal fluid (CSF) and sera samples from patients in the following stages of syphilis were tested: 8 had symptomatic and 16 asymptomatic neurosyphilis, 4 were in the primary stage, 6 had secondary syphilis, and 92 were in the latent stage. We have also studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 22 publications
2
46
1
7
Order By: Relevance
“…Our findings are consistent with the reports from Castro et al (5) regarding the performance of CSF-RPR and Jiang et al regarding the CSF-TRUST, which involved 24 and 41 neurosyphilis patients, respectively (6). In an earlier study in 1985, Larsen et al concluded that CSF-RPR and CSF-TRUST had statistically significantly lower sensitivities and specificities than CSF-VDRL; how- ever, their study was limited by a small sample of patients and older diagnostic techniques (14).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with the reports from Castro et al (5) regarding the performance of CSF-RPR and Jiang et al regarding the CSF-TRUST, which involved 24 and 41 neurosyphilis patients, respectively (6). In an earlier study in 1985, Larsen et al concluded that CSF-RPR and CSF-TRUST had statistically significantly lower sensitivities and specificities than CSF-VDRL; how- ever, their study was limited by a small sample of patients and older diagnostic techniques (14).…”
Section: Discussionsupporting
confidence: 94%
“…Compared to VDRL, the rapid plasma reagin test (RPR) and the toluidine red unheated serum test (TRUST) have similar test principles and performance using serum specimens, are easier to perform, and are available as commercial test kits (5,6). RPR and TRUST may be promising alternatives to VDRL when testing CSF for neurosyphilis; however, their use in routine clinical practice is currently controversial because of limited experience and published reports in the literature.…”
mentioning
confidence: 99%
“…Patient characteristics are depicted in Table 1. In this study, we considered a positive CSF-RPR as the gold standard for diagnosing neurosyphilis (5,6). According to the Dutch legislature (Evaluation of the Dutch Medical Treatment Act…”
Section: Methodsmentioning
confidence: 99%
“…When dual infections with HIV and syphilis exist, the diagnostic challenge increases. A positive cerebrospinal fluid (CSF) Venereal Disease Research Laboratory test (VDRL) is generally considered the gold standard for neurosyphilis (4); however, several studies have clearly shown that a positive CSF rapid plasma reagin test (RPR) is an alternative to CSF-VDRL (5,6), and RPR is also recommended by 2014 European guidelines (IUSTI-2014) (7). When the CSF-RPR or CSF-VDRL is negative, the diagnosis relies on other markers, like CSF pleocytosis, the CSF T. pallidum particle agglutination (TPPA) index, and clinical signs and symptoms.…”
mentioning
confidence: 99%
“…Castro y cols., demostraron que RPR en LCR tiene sensibilidad 75% contra VDRL 70,8% y la especificidad del 99% contra 99,3%, respectivamente, además la RPR es pronta y cuesta menos 40 . La sola presencia de anticuerpos treponémicos no garantiza el diagnóstico de NS, porque puede ser resultado de la difusión pasiva sangre-LCR, más que por actividad de la sífilis cerebral 2,41 .…”
Section: Demencia Paralítica Progresiva (Dpp)unclassified